Oil volatility risk - Gao, Lin; Hitzemann, Steffen; Shaliastovich, Ivan; Xu, Lai (Journal of Financial Economics, 2022)
The option-implied oil price volatility is a strong negative predictor of economic growth beyond traditional uncertainty measures. A rise in oil volatility also predicts an increase in oil inventories and a reduction in oil consumption, in line with a propagation channel through the oil sector. We explain these findings within a macro-finance model featuring stochastic uncertainties and precautionary oil inventories: firms increase oil inventories when oil volatility rises, which curbs oil use for production and depresses economic activity. In the model and the data, aggregate equity prices fall at times of high oil volatility, with differential exposures across economic sectors.